2017
DOI: 10.1039/c7ra08324f
|View full text |Cite
|
Sign up to set email alerts
|

Is nano ZrO2 a better photocatalyst than nano TiO2 for degradation of plastics?

Abstract: The environmental accumulation of plastic is a huge problem due to its low degradability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 42 publications
(42 reference statements)
0
20
0
Order By: Relevance
“…88,89 This strategy generally uses oxide semiconductor materials (TiO 2 , ZnO, ZrO 2 , etc.) [90][91][92][93][94] as photocatalysts for polyolefin decomposition, but their performances are always unsatisfactory. Thus, the urgent task in this field is the increase of activity.…”
Section: Photocatalysismentioning
confidence: 99%
“…88,89 This strategy generally uses oxide semiconductor materials (TiO 2 , ZnO, ZrO 2 , etc.) [90][91][92][93][94] as photocatalysts for polyolefin decomposition, but their performances are always unsatisfactory. Thus, the urgent task in this field is the increase of activity.…”
Section: Photocatalysismentioning
confidence: 99%
“…Their findings show that 78% of PE degrades in 15 days of reaction. Bandara et al, (2017) reported the degradation of plastic over TiO 2 and ZrO 2 under sunlight. In this case, the degradation of PE and PP were studied in terms of its morphology and changes in carbonyl index.…”
Section: Journal Of Sustainability Science and Management Volume 15 Nmentioning
confidence: 99%
“…The SEM micrograph of PP plastic after being treated for five times as indicated in Figure 8. The damage of the PP surface increases with increased exposure to light source and longer reaction time (Bandara et al, 2017).…”
Section: The Influence Of Cyclic Thermo-photocatalytic Treatment On Pmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, there is a need for an environmental purification technology that has little or no maintenance cost. A representative technology that meets this requirement is the application of photocatalysts [3][4][5][6][7][8]. Photocatalysts show tremendous potentials for degradation of toxic contaminants and dyes, and they are recognized as one of the most efficient means to solve the issue of environmental pollution [9].…”
Section: Introductionmentioning
confidence: 99%